A double-doped sodium iron sulfate positive electrode material and its preparation method and application
By reacting pyroferrous sulfate and sodium hydroxide in an oxygen environment, the double-doped sodium ferrous sulfate positive electrode material is solved, and the good electrochemical performance of high-performance sodium ion batteries is achieved at high and low temperatures.
Patent Information
- Application Number
- CN202411747817.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing sodium ferric sulfate positive electrode materials have poor conductivity and stability, which cannot meet the needs of high-performance sodium ion batteries, and the cycle stability and capacity retention rate in high and low temperature environments are insufficient.
Using pyroferite as raw material, a double-doped sodium ferrous sulfate positive electrode material was prepared by reacting with ferrous sulfate and sodium hydroxide under an oxygen environment, and the chemical formula is Na2+aFe2-b-cTMc(SO4)3-d(SeO4)d, where TM includes cobalt and nickel.
The conductivity, stability, rate performance and high and low temperature electrochemical properties of the cathode material are significantly improved. The assembled batteries obtain high operating voltage and excellent discharge specific capacity, especially at temperatures of 50°C and -5°C.
Smart Images

Figure CN119230826B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a double-doped sodium iron sulfate positive electrode material and a preparation method and application thereof. Background Art
[0002] Sodium ferric sulfate (chemical formula is Na 2+x Fe 2-y (SO4)3, x = 0~0.5, y = 0~0.25) has the advantages of abundant raw material resources, low cost, and high charge and discharge platform, and has a place in the application of sodium ion battery energy storage. Sodium ferric sulfate exhibits a high charge and discharge voltage platform due to the large inductive effect of sulfate ions, but the conductivity of this type of material is poor, and additional doping and other means are usually required to optimize the performance. The current mainstream industrial synthesis method of sodium ferric sulfate is to pretreat ferrous sulfate heptahydrate and anhydrous sodium sulfate to obtain anhydrous ferrous sulfate and anhydrous sodium sulfate, and then solid-phase sintering at about 350°C (ACS Applied Materials & Interfaces, 2016, 8, 6982). Such a synthesis method requires a pretreatment step, the processing steps are complex and costly, the energy consumption is large, and the conductivity and stability of the product are poor. Another method is to dissolve ferrous sulfate heptahydrate and anhydrous sodium sulfate in an aqueous solution and spray dry them to obtain a precursor, and then perform low-temperature solid-phase sintering (Electrochimica Acta, 2019, 296, 345). The conductivity and rate performance of the sodium iron sulfate cathode material synthesized by the above synthesis method are poor, and cannot meet the use requirements of high-performance sodium ion batteries. At the same time, with the continuous expansion of the application field of sodium ion batteries, the market has higher and higher performance requirements in the high and low temperature fields. At present, the cycle stability of sodium iron sulfate above 50°C is poor, and at -5°C and below, its capacity is difficult to maintain above 100 mAh / g. Summary of the invention
[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a positive electrode material.
[0004] A second object of the present invention is to provide a method for preparing a positive electrode material.
[0005] A third object of the present invention is to provide a battery.
[0006] A fourth object of the present invention is to provide a product containing a battery.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a positive electrode material, the positive electrode material comprising a doped sodium iron sulfate material; the chemical formula of the doped sodium iron sulfate material is Na 2+a Fe 2-b-c TM c (SO4) 3-d (SeO4) d , wherein TM includes at least one of cobalt and nickel; a = 0~1; b = 0~0.5, b = 0.5a; c = 0~1, and not 0; d = 0~0.2, and not 0.
[0009] In the present invention, a=0~1, for example, a can be selected from 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1; preferably, a=0.1~0.8, more preferably, a=0.28~0.5.
[0010] In the present invention, b = 0~0.5, for example, b can be selected from 0, 0.1, 0.2, 0.3, 0.4, 0.5; preferably, b = 0.05~0.4; more preferably, b = 0.14~0.25.
[0011] In the present invention, c = 0~1, and is not 0, for example, c can be selected from 0.01, 0.1, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1; preferably, c = 0.1~0.5; more preferably, c = 0.2~0.35.
[0012] In the present invention, d=0~0.2, and is not 0, for example, d can be selected from 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2; preferably, d=0.01~0.15; further preferably, d=0.05~0.1.
[0013] Preferably, the chemical formula of the doped sodium iron sulfate material is Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 、Na 2.4 Fe 1.55 (CoNi)0.25 (SO4) 2.94 (SeO4) 0.06 、 2.38 Fe 1.55 (CoNi) 0.26 (SO4) 2.94 (SeO4) 0.06 、 2.36 Fe 1.55 (CoNi) 0.28 (SO4) 2.93 (SeO4) 0.07 、 2.34 Fe 1.54 (CoNi) 0.29 (SO4) 2.93 (SeO4) 0.07 、Na 2.32 Fe 1.52 (CoNi) 0.31 (SO4) 2.92 (SeO4) 0.08 、Na 2.30 Fe 1.52 (CoNi) 0.33 (SO4) 2.92 (SeO4) 0.08 、Na 2.28 Fe 1.51 (CoNi) 0.35 (SO4) 2.91 (SeO4) 0.09 ; Further preferably, the chemical formula of the doped sodium iron sulfate material is Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 .
[0014] The second aspect of the present invention provides a method for preparing the positive electrode material according to the first aspect of the present invention, comprising the following steps:
[0015] S1: grinding pyrite and ferrous sulfate and mixing with sodium hydroxide to obtain a precursor;
[0016] S2: The precursor and the oxygen generator are placed separately in a closed environment and then heated to react to obtain the positive electrode material.
[0017] The present invention uses pyrite as one of the raw materials. Pyrite has a wide source and low cost. Pyrite contains impurity selenium, which can replace the site of S to form SeO4. 2-Ions, Ni and / or Co in pyrite can be doped into the prepared sodium iron sulfate to form a doped sodium iron sulfate material. The specific reaction formula is as follows:
[0018] 2FeS2+7O2+4NaOH+2FeSO4=2Na2Fe2(SO4)3+2H2O (Formula 1)
[0019] 2.5FeS2+8.75O2+5NaOH+FeSO4=2Na 2.5 Fe 1.75 (SO4)3+2.5H2O (Formula 2)
[0020] 2Fe 1-x TM x Se y S 2-y +7O2+4NaOH+2FeSO4=2Na2Fe 2-x TM x (SO4) 3-y (SeO4) y +2H2O (Formula 3)
[0021] 2.5Fe 1-x TM x Se y S 2-y +8.75O2+5NaOH+FeSO4=2Na 2.5 Fe 1.75-x TM x (SO4) 3-y (SeO4) y +2.5H2O (Formula 4)
[0022] 2Na2O2=2Na2O+O2 (Formula 5)
[0023] Na2O+H2O=2NaOH (Formula 6)
[0024] in:
[0025] Formula 1 is a chemical reaction equation for preparing an ideal sodium iron sulfate that meets the stoichiometric ratio using high-purity FeS2 as a raw material.
[0026] Formula 2 is the chemical reaction equation for preparing non-stoichiometric sodium iron sulfate using high-purity FeS2 as raw material.
[0027] Formula 3 is a chemical reaction equation for preparing double-site doped sodium iron sulfate that meets the stoichiometric ratio using pyrite as a raw material.
[0028] Formula 4 is a chemical reaction equation for preparing dual-site doped, non-stoichiometric sodium iron sulfate using pyrite as a raw material.
[0029] In formula 3-4, TM is the native trace 3d transition metal element cobalt, nickel, etc. in the pyrite raw material.
[0030] Formula 5 is a chemical reaction equation for providing the oxygen required by Formula 1-4. Therefore, any one of the reactions in Formula 1-4 must be performed in the same time and space as Formula 5.
[0031] Formula 6 is a process in which the product of Formula 5 dehumidifies the reaction environment after the reaction represented by any one of Formulas 1-4 and Formula 5 is completed. This process can effectively absorb the water molecules generated by Formulas 1-4 to prevent residual moisture from adversely affecting the product sodium iron sulfate.
[0032] Preferably, the molar ratio of the pyrite to ferrous sulfate is 1:1 to 5:1, for example, can be selected from 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.7:1, 2.9:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.6:1, 4.8:1 or 5:1.
[0033] Preferably, the molar ratio of sodium hydroxide to ferrous sulfate is 2:1 to 6:1, for example, can be selected from 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1.
[0034] Preferably, the molar ratio of the oxygen generator to ferrous sulfate is 7:1-17.5:1, for example, can be selected from 7:1, 9:1, 11:1, 13:1, 15:1, 17:1 or 17.5:1.
[0035] Preferably, the oxygen generator is selected from at least one of sodium peroxide, potassium peroxide, potassium permanganate and calcium peroxide. In the present invention, sodium peroxide is used as an oxygen generator to provide a source of oxygen for the reaction, and as a moisture absorbent to absorb moisture generated by the reaction.
[0036] Preferably, the temperature-raising reaction step in step S2 is: firstly heating to 50-200°C for the first stage reaction, and then heating to 200-500°C for the second stage reaction. The first stage reaction temperature is 50-200°C, for example, it can be selected from 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C. The second stage reaction temperature is 200-500°C, for example, it can be selected from 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C.
[0037] Preferably, the heating rate of the first stage reaction is 1-20°C / min, for example, can be selected from 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min.
[0038] Preferably, the first stage reaction time is 1 to 24 h, for example, can be selected from 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h.
[0039] Preferably, the heating rate of the second stage reaction is 1-20°C / min, for example, can be selected from 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min.
[0040] Preferably, the time of the second stage reaction is 4 to 48 hours, for example, can be selected from 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 26h, 28h, 30h, 32h, 33h, 34h, 36h, 38h, 40h, 42h, 43h, 44h, 46h or 48h.
[0041] In the first stage of the reaction, the ball milling medium and adsorbed water that are weakest in bonding with the raw materials are evaporated first and flow with the airflow; in the second stage of the reaction, the oxygen generator begins to produce oxygen, and the sodium hydroxide melts at about 330°C into a solution that evenly covers the ferrous sulfate and ferrous disulfide, undergoes a sintering reaction, and forms a sodium ferric sulfate positive electrode material in an oxygen atmosphere. After the heating is completed, it is cooled naturally, and the water produced by the reaction is absorbed by the solid products remaining after the decomposition of the oxygen generator (such as the solid sodium oxide remaining after the decomposition of sodium peroxide), ensuring a low humidity environment during the cooling process and preventing the sodium ferric sulfate powder from being corroded by moisture.
[0042] Preferably, the grinding step is performed by ball milling; more preferably, the grinding step is performed by wet ball milling.
[0043] Preferably, the ball mill rotation speed is 100-600 r / min, for example, can be selected from 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min or 600 r / min.
[0044] Preferably, the ball milling time is 1 to 600 min, for example, can be selected from 1 min, 10 min, 50 min, 100 min, 150 min, 200 min, 250 min, 300 min, 350 min, 400 min, 450 min, 500 min, 550 min or 600 min.
[0045] Preferably, a dispersant is added for dispersion during the wet ball milling.
[0046] Preferably, the dispersant is selected from at least one of ethanol, acetone, isobutanol, ethylene glycol, polyethylene glycol (PEG), polyacrylic acid (PAA), polyvinyl pyrrolidone (PVP), sodium polystyrene sulfonate (PSS), triethanolamine (TEA), sodium citrate, polyvinyl alcohol (PVA), polyethylene glycol monomethyl ether (MPEG), and polyethylene oxide (PEO); further preferably, the dispersant is anhydrous ethanol.
[0047] Preferably, the step S2 is: placing the precursor in an alkali-resistant crucible, placing the oxygen generator in a porcelain boat, and then placing them in a closed tubular furnace respectively, evacuating the furnace and heating them for reaction, and naturally cooling and demagnetizing them after the reaction to obtain the positive electrode material.
[0048] Preferably, the material of the alkali-resistant crucible is selected from quartz, graphite, ceramic, platinum, aluminum oxide, zirconium oxide, silicon carbide, corundum, silicon nitride, mullite, magnesium oxide or aluminum oxynitride. Further preferably, the alkali-resistant crucible is a graphite crucible.
[0049] The third aspect of the present invention provides a battery, comprising the positive electrode material described in the first aspect of the present invention.
[0050] The fourth aspect of the present invention provides a battery-containing product, including the battery described in the third aspect of the present invention; the product is selected from a mobile electronic communication device, an electric vehicle, an electric bicycle, an energy storage battery, a power battery or an energy storage power station.
[0051] The beneficial effect of the present invention is that the positive electrode material of the present invention adopts Se and TM (such as cobalt and / or nickel) to simultaneously dope sodium iron sulfate material, which significantly improves the conductivity, stability, rate performance and electrochemical performance of the positive electrode material at high and low temperatures. The battery assembled with the positive electrode material prepared in the present invention obtains a higher working voltage and a better discharge specific capacity, specifically: the working voltage is 2-4.5 V, the initial capacity at room temperature 1C is 109.8-116.8 mAh / g, the capacity retention rate of 5000 cycles is 72-84%, and the capacity retention rate of 10000 cycles at 5C is 40-59%; the initial capacity at 50°C and 1C is 114-117 mAh / g, and the capacity retention rate of 1000 cycles is 64-71%; the initial capacity at -5°C and 1C is 96-103 mAh / g, and the capacity retention rate of 500 cycles is 71-76%.
[0052] The preparation method of the present invention introduces pyrite and sodium hydroxide as raw materials for the first time, and reacts in an oxygen environment to obtain sodium ferric sulfate. Since natural pyrite contains trace amounts of transition metal elements (TM, such as cobalt, nickel, etc.) and sulfide elements (selenium), the sulfide elements doping the sulfur sites of sodium ferric sulfate can improve the conductivity of the material, and the TM elements doping the iron sites of sodium ferric sulfate can improve the stability of the material, so that the rate performance, cycle stability and high and low temperature performance of the synthesized product double-site doped sodium ferric sulfate are significantly improved. Compared with other synthesis methods, the preparation method of the present invention has simple synthesis steps and low energy consumption. Pyrite is used as both an iron source and a doped transition metal source and selenium source, taking into account both the synthesis and doping functions; the prepared double-doped sodium ferric sulfate positive electrode has high conductivity, good rate performance, good cycle stability, and excellent high and low temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Schematic diagram of the structure of the tube furnace used in the embodiment of the present invention.
[0054] Figure 2 Schematic diagram of the partial structure of the tube furnace used in the embodiment of the present invention.
[0055] Figure 3 This is the XRD test diagram of the positive electrode material in Example 1 of the present invention.
[0056] Reference numerals:
[0057] Furnace body 1; furnace tube 2; electric heating element 3; alkali-resistant crucible 4; porcelain boat 5; air outlet 6; switch 7; pressure gauge 8; flange 9; high-temperature insulation layer 10; furnace tube bracket 11; panel switch 12; instrument 13; temperature controller 14. DETAILED DESCRIPTION
[0058] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0059] The structural schematic diagram of the tube furnace used in the preparation method in the embodiment and comparative example of the present invention is as follows Figure 1 The local structure diagram is shown in Figure 2 As shown; the alkali-resistant crucible 4 in the furnace tube 2 is made of a quartz crucible that is resistant to high temperature and alkali corrosion.
[0060] The pyrite used in the embodiment of the present invention is tested by inductively coupled plasma-mass spectrometry (ICP-MS), and it is known that the pyrite contains Se, Co and Ni elements at the same time.
[0061] Example 1
[0062] This example provides a method for preparing a double-doped sodium iron sulfate positive electrode material, comprising the following steps:
[0063] 1) Weigh 0.11 mol of pyrite and 0.044 mol of ferrous sulfate respectively; put them in a ball mill, add anhydrous ethanol, and ball mill at a speed of 300 r / min for 300 min to obtain a pyrite-ferrous sulfate mixture, then weigh 0.22 mol of sodium hydroxide and mix it with the pyrite-ferrous sulfate to obtain a precursor, which is placed in an alkali-resistant crucible 4.
[0064] 2) Weigh 0.64 mol Na2O2 into a porcelain boat 5, and place it together with the above-mentioned alkali-resistant crucible 4 in a tube furnace. After evacuation, heat it to 80°C (T1) at 5°C / min (V1), and keep it warm for 5h (t1); then heat it to 350°C (T2) at 5°C / min (V2), and keep it warm for 24h (t2). Finally, turn off the power, cool it naturally, and after demagnetization, obtain the double-doped sodium iron sulfate positive electrode material in this example.
[0065] The double-doped sodium iron sulfate cathode material prepared in this example has a molecular formula of Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 ; X-ray diffractometer was used to test the double-doped sodium iron sulfate positive electrode material in this example and the standard Na 2.5 Fe 1.75 X-ray diffraction pattern of (SO4)3 sample, specific test results are as follows Figure 3 As shown. Figure 3 It can be seen that the Na prepared in this example 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 Cathode materials and standard Na 2.5 Fe 1.75 The diffraction peaks of the (SO4)3 sample are consistent, indicating that the present invention successfully prepared Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 Positive electrode material.
[0066] Example 2-22
[0067] The dual-doped sodium iron sulfate positive electrode materials in Examples 2 to 22 can be prepared by referring to the preparation method in Example 1, and the specific experimental conditions are recorded in Table 1 below.
[0068] Table 1 Specific experimental conditions of Examples 1-22
[0069]
[0070] Examples 23-29
[0071] The preparation method of the dual-doped sodium iron sulfate positive electrode material in Examples 23 to 29 is different from that in Example 1 only in that the dosage ratio of pyrite and sodium hydroxide in step (1) is adjusted in Examples 23 to 29, as shown in Table 2 below.
[0072] Table 2 Specific experimental conditions of Examples 23-29
[0073]
[0074] Embodiment 30
[0075] This example provides a sodium ion half-cell, the positive electrode active material of which is the double-doped sodium iron sulfate positive electrode material prepared in Example 1, that is, the molecular formula is Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 Cathode materials;
[0076] The sodium ion half-cell in this example is prepared by a preparation method comprising the following steps, specifically:
[0077] (1) Preparation of battery positive electrode: 1.8 g of Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 Add the positive electrode material powder and 0.2 g of polyvinylidene fluoride to 2 mL of nitrogen methyl pyrrolidone and grind thoroughly to obtain a uniform slurry; evenly coat the slurry on the surface of aluminum foil (positive electrode current collector) and vacuum dry. Cut the dried electrode sheet into a disc with a diameter of 10 mm, compact it and use it as the positive electrode sheet of the battery;
[0078] (2) Preparation of diaphragm: Cut the glass fiber film into discs with a diameter of 16 mm and use them as diaphragms;
[0079] (3) Preparation of electrolyte: Weigh 3.0313 g of sodium bis(fluorosulfonyl)imide and dissolve it in a mixed solvent of 6 mL of ethyl acetate and 4 mL of fluoroethylene carbonate. Mix thoroughly and use it as the electrolyte for later use.
[0080] (4) Preparation of battery negative electrode: Press the sodium metal into thin sheets and cut into 12 mm diameter discs to serve as the battery negative electrode;
[0081] (5) Battery assembly: In an inert gas-protected glove box, the prepared positive electrode, separator and negative electrode are stacked tightly in sequence, and the electrolyte is added dropwise to completely soak the separator. The stacked parts are then encapsulated into a button-type battery casing to complete the battery assembly and obtain the sodium ion half-cell in this example.
[0082] Examples 31-58
[0083] The preparation method of the sodium ion half-cell in Examples 31-58 is different from that in Example 30 only in that Examples 31-58 respectively use the double-doped sodium iron sulfate positive electrode material in Examples 2 to 29 as the positive electrode active material.
[0084] Comparative Example 1
[0085] The preparation method of the sodium iron sulfate positive electrode material in this example is different from that in Example 1 only in that analytically pure FeS2 is used in this example instead of the pyrite in Example 1.
[0086] Comparative Example 2
[0087] The sodium iron sulfate positive electrode material in this example is prepared by a preparation method comprising the following steps, specifically:
[0088] (1) Weigh 0.1 mol of anhydrous sodium sulfate and 0.1 mol of anhydrous ferrous sulfate respectively, put them into a ball mill, add anhydrous ethanol, and ball mill at a speed of 300 r / min for 300 min to obtain a sodium sulfate-ferrous sulfate mixture;
[0089] (2) The sodium sulfate-ferrous sulfate mixture is sintered at 350° C. for 24 hours to obtain the sodium ferrous sulfate positive electrode material in this example.
[0090] Comparative Example 3
[0091] The preparation method of the sodium ion half-cell in this example is different from that in Example 30 only in that this example uses the sodium iron sulfate positive electrode material prepared in Comparative Example 1 as the positive electrode active material.
[0092] Comparative Example 4
[0093] The preparation method of the sodium ion half-cell in this example is different from that in Example 30 only in that this example uses the sodium iron sulfate positive electrode material prepared in Comparative Example 2 as the positive electrode active material.
[0094] The positive electrode materials prepared in Examples 1 to 29 and Comparative Examples 1 to 2 were tested respectively, the molecular formula was obtained by ICP-MS and the impurity content was obtained by XRD refinement. The specific test results are shown in Table 3 below.
[0095] Table 3 Molecular formula and impurity content test results of positive electrode materials
[0096]
[0097] As can be seen from Table 3, the present invention uses pyrite, ferrous sulfate, sodium hydroxide and sodium peroxide as reaction raw materials, controls various parameter conditions in the reaction process, and synthesizes a series of sodium ion battery positive electrode materials with different molecular formulas through a one-step solid phase method. The impurity content in the sodium ion battery positive electrode material is extremely low, about 3.5-8%; the types of impurities are slightly different, and the common ones are sodium sulfate, ferrous oxide, and ferrosoferric oxide.
[0098] Then, the constant current charge and discharge performance of the sodium ion half-cells prepared in Examples 30-58 and Comparative Examples 3-4 was tested. The loading amount of the positive electrode active material of the positive electrode of the battery was 2-4 mg / cm 2 , the test voltage range is 2-4.5 V, other test methods are:
[0099] (1) Constant-current charge and discharge test at room temperature: The BTSDA test system of Shenzhen Xinwei Electronics Co., Ltd. was used in a constant temperature and humidity room (temperature: 25°C, humidity: 35%); 10 cycles at 0.1C, and then long-cycle performance test at 1C or 5C. The initial specific capacity refers to the discharge specific capacity of the first cycle; the capacity retention rate refers to the ratio of the capacity at the end of the cycle to the capacity at the 11th cycle.
[0100] (2) High temperature constant current charge and discharge test: The DWH-60-100 high and low temperature constant temperature test chamber of Cangzhou Xinxing Testing Instrument Co., Ltd. is used, and the test temperature is 50℃.
[0101] (3) Low temperature constant current charge and discharge test: The DWH-60-100 high and low temperature constant temperature test chamber of Cangzhou Xinxing Testing Instrument Co., Ltd. is used, and the test temperature is -5°C.
[0102] The test results obtained according to the above test method are shown in Table 4.
[0103] Table 4 Performance test results of sodium ion half-cell
[0104]
[0105] As shown in Table 4, the present invention assembles the sodium ion battery cathode materials prepared in Examples 1 to 29 into sodium ion half-cells, and obtains a higher operating voltage and a better discharge specific capacity, specifically: the operating voltage is 2-4.5 V, the initial capacity at room temperature 1C is 109.8-116.8 mAh / g, the capacity retention rate of 5000 cycles is 72-84%, and the capacity retention rate of 10000 cycles at 5C is 40-59%; at 50°C, the initial capacity at 1C is 114-117 mAh / g, and the capacity retention rate of 1000 cycles is 64-71%; at -5°C, the initial capacity at 1C is 96-103 mAh / g, and the capacity retention rate of 500 cycles is 71-76%. In addition, Example 30 has achieved electrochemical performance at room temperature and high and low temperatures that is significantly better than that of other examples.
[0106] As shown in Tables 1 to 4, Examples 1 to 5 are to explore the molecular formula of Na obtained by different proportions of raw materials. 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 The positive electrode material of the sodium ion battery, embodiments 30 to 34 are sodium ion half-cells assembled using the positive electrode materials obtained in embodiments 1 to 5. It is found that different proportions of raw materials have a greater impact on the purity of the material, thereby having a greater impact on its cycle performance. When the content of sodium hydroxide is too much or too little, the content of impurities in the finally obtained sodium ferric sulfate material will increase, and when the impurity content is too much, the rate and cycle stability of the assembled sodium ion half-cell will decrease. When the content of sodium peroxide is too low, the oxidation will be insufficient, and when the content of sodium peroxide is too high, it will cause the divalent iron to be oxidized to produce trivalent iron, and the impurity content will increase. Therefore, in order to obtain better rate performance and better cycle performance, the molar ratio of sodium hydroxide, sodium peroxide and pyrite is 2.2: 6.4: 1.1, which is a better choice.
[0107] Examples 6 to 12 are to explore the Na obtained by different ball milling speeds and ball milling times. 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 Examples 35 to 41 are sodium ion half-cells assembled with the positive electrode materials obtained in Examples 6 to 12. It is found that the ball milling speed and ball milling time have little effect on the main components of the materials, but the rate and cycle stability of the corresponding sodium ion half-cells are slightly deviated. It is speculated that the possible reason is that the ball milling speed and ball milling time have a comprehensive effect on the particle morphology, particle size, etc. of the positive electrode material.
[0108] Examples 13 to 22 are to explore the effects of different temperature regimes (temperature, heating rate, and holding time) on the product Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 Influence, Examples 42 to 51 are sodium ion half-cells assembled using the positive electrode materials obtained in Examples 13 to 22, respectively. When the first stage heating temperature is too low, the ball milling medium and water are not fully volatilized, resulting in a high impurity content; at the same time, when the second stage heating temperature is too low, the reaction is slow and the impurity content increases. When the first stage heating temperature is too high, sodium peroxide produces oxygen in advance and reacts with pyrite at low temperatures to produce impurities; when the second stage heating temperature is too high, Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 The instability leads to partial decomposition, resulting in reduced product purity. The heating rate has little effect on the product. Considering energy consumption and efficiency, 5°C / min is preferred. At the same time, based on the comparison of product purity, cycle stability and rate performance, the preferred temperature system is to heat to 80°C in the first stage and keep it for 5 hours; and to heat to 350°C in the second stage and keep it for 24 hours.
[0109] Examples 23 to 29 explore the effects of different ratios of pyrite to sodium hydroxide on the positive electrode materials, and Examples 52 to 58 are sodium ion half-cells assembled using the positive electrode materials obtained in Examples 23 to 28, respectively. It can be seen that with the relative increase in the proportion of pyrite, the content of doping elements Co, Ni, and Se in the product increases, and the content of Na decreases; in addition, the impurity content of the product increases, resulting in the electrochemical performance of the corresponding positive electrode materials being inferior to that of Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 .
[0110] Comparative Examples 3 and 4 respectively use the Na2O3 prepared in Comparative Examples 1 and 2 without doping with cobalt, nickel and selenium. 2.5 Fe 1.75 The electrochemical performance of (SO4)3 and Na2Fe2(SO4)3 shows that the rate performance and cycle stability of both are lower than those of Examples 23-44. 2.5 Fe 1.75 The electrochemical performance of (SO4)3 is slightly higher than that of Na2Fe2(SO4)3.
[0111] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a doped sodium iron sulfate material; the chemical formula of the doped sodium iron sulfate material is Na 2+a Fe 2-b-c TM c (SO4) 3-d (SeO4) d , Among them, TM c Selected from (CoNi) c ; a=0.28~0.5; b = 0.14~0.25, b = 0.5a; c=0.2~0.35; d=0.05~0.09。 2. The positive electrode material according to claim 1, characterized in that: The chemical formula of the doped sodium iron sulfate material is Na 2.5 Fe 1.55 (CoNi) 0.2 (SO4) 2.95 (SeO4) 0.05 、Na 2.4 Fe 1.55 (CoNi) 0.25 (SO4) 2.94 (SeO4) 0.06 、Na 2.38 Fe 1.55 (CoNi) 0.26 (SO4) 2.94 (SeO4) 0.06 、 2.36 Fe 1.55 (CoNi) 0.28 (SO4) 2.93 (SeO4) 0.07 、Na 2.34 Fe 1.54 (CoNi) 0.29 (SO4) 2.93 (SeO4) 0.07 、Na 2.32 Fe 1.52 (CoNi) 0.31 (SO4) 2.92 (SeO4) 0.08 、Na 2.30 Fe 1.52 (CoNi) 0.33 (SO4) 2.92 (SeO4) 0.08 、Na 2.28 Fe 1.51 (CoNi) 0.35 (SO4) 2.91 (SeO4) 0.09 One of them.
3. The method for preparing the positive electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: grinding pyrite and ferrous sulfate and mixing with sodium hydroxide to obtain a precursor; S2: The precursor and the oxygen generator are placed separately in a closed environment and then heated to react to obtain the positive electrode material.
4. The method for preparing the positive electrode material according to claim 3, characterized in that: The molar ratio of the pyrite to ferrous sulfate is 1:1 to 5:
1.
5. The method for preparing the positive electrode material according to claim 3, characterized in that: The molar ratio of the sodium hydroxide to the ferrous sulfate is 2:1 to 6:
1.
6. The method for preparing the positive electrode material according to claim 3, characterized in that: The molar ratio of the oxygen generator to ferrous sulfate is 7:1 to 17.5:
1.
7. The method for preparing the positive electrode material according to claim 3, characterized in that: The temperature-raising reaction step in step S2 is: firstly raising the temperature to 50-200° C. for the first stage reaction, and then raising the temperature to 200-500° C. for the second stage reaction.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The heating rate of the first stage reaction is 1-20°C / min; the reaction time of the first stage is 1-24h.
9. The method for preparing the positive electrode material according to claim 7, characterized in that: The heating rate of the second stage reaction is 1-20°C / min; the reaction time of the second stage is 4-48h.
10. The method for preparing the positive electrode material according to claim 3, characterized in that: The oxygen generator is selected from at least one of sodium peroxide, potassium peroxide, potassium permanganate and calcium peroxide.
11. The method for preparing the positive electrode material according to claim 3, characterized in that: The step S2 is: placing the precursor in an alkali-resistant crucible, placing the oxygen generator in a porcelain boat, and then placing them in a closed tubular furnace respectively, evacuating the furnace, heating the furnace for reaction, and removing magnetism to obtain the positive electrode material.
12. A battery, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 2.
13. A product, characterized in that: Including the battery according to claim 12; the product is selected from mobile electronic communication equipment, electric vehicles, electric bicycles, energy storage batteries, power batteries or energy storage power stations.
Citation Information
Patent Citations
Non-destructive fast-charging positive electrode material based on ultra-small particle NaxFeyMz (SO4) 3 and preparation method and application of non-destructive fast-charging positive electrode material
CN116706056A
KR20200032662A